2014
DOI: 10.1021/nn405398d
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface

Abstract: Controlled release system based on mesoporous silica (MS) nanomaterials has drawn great attention over the past decades due to its potential biomedical applications. Herein, a light-responsive release system based on MS nanoparticles was achieved by adjusting the wetting of the MS surface. At the starting stage, the surface of MS modified with optimal ratio of spiropyran to fluorinated silane (MS-FSP) was protected from being wetted by water, successfully inhibiting the release of model cargo molecules, fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 49 publications
0
69
0
3
Order By: Relevance
“…Yildrim et al reported that mesoporous silica nanoparticles are effective ultrasound contrast agents, by releasing or nucleating microbubbles in response to focused ultrasound [225]. Finally, Chen et al synthesized mesoporous silica nanoparticles with grafted fluorocarbons and photoresponsive spiropyran [226]. The authors showed UV-triggered release of loaded fluorescein disodium and camptothecin.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Yildrim et al reported that mesoporous silica nanoparticles are effective ultrasound contrast agents, by releasing or nucleating microbubbles in response to focused ultrasound [225]. Finally, Chen et al synthesized mesoporous silica nanoparticles with grafted fluorocarbons and photoresponsive spiropyran [226]. The authors showed UV-triggered release of loaded fluorescein disodium and camptothecin.…”
Section: Drug Deliverymentioning
confidence: 99%
“…This structural conversion of spiropyran from hydrophobic to hydrophilic can induce significant solubility change for photo-triggered therapy and imaging. For instance, Chen and co-workers reported a light responsive drug release MSNs nanoplatform by adjusting the wetting behavior of hydrophobic surface 60. Briefly, the surface of spiropyran modified MSNs were protected from being wetted by water which could successfully inhibit the release of anticancer drug (CPT).…”
Section: Uv Light-mediated Theranosticsmentioning
confidence: 99%
“…[1][2][3] One such smart material is the stimuliresponsive polymeric surface with tunable wettability under different external conditions, 4 such as pH, 5-8 electric potential, 9,10 light, [11][12][13][14] temperature, [15][16][17][18] and gas. 19 This feature enables the material to have applications in many areas, including controlled release platform, 20 ion pump, 21 and water/oil separation. [22][23][24] pH-responsive method is an attractive method to trigger the change of wettability due to its rapid response process.…”
Section: Introductionmentioning
confidence: 99%